Flexible nanoscale memory device based on resistive switching in nickel oxide thin film - Yu, Q. (2013)
In this work, a flexible memory device based on resistive switching in a NiO thin film has been demonstrated. A large memory window with the resistance ratio of ∼103 between the high-resistance state and the low-resistance state is observed. A memory state can be altered by either voltage pulses or a voltage sweeping. The memory window can be maintained in repetitive programming/erase cycles (at least 120 cycles have been demonstrated in the present experiment), showing a good endurance. In addition, in the time frame (104 s) of the retention experiment, no significant degradation in the memory window is observed, demonstrating a good retention capability.